H alpha line measurements from ten diffuse galactic sources using the DEFPOS facility - Sahan, M.; OFLAZ, F; Yegingil, Ilhami; Tel, Eyyup (WILEY-V C H VERLAG GMBH, 2015)
The hydrogen Balmer-alpha emission line spectrum of ten diffuse ionization sources in the Milk Way - NGC 40 (WC8), NGC 2022, NGC 6210, NGC 6618 (M17, Sh2-45), NGC 6720 (M57), NGC 6781, NGC 6888 (Sh2-105), NGC 6992 (Sh2-103), NGC 7635 (Sh2-162,) and IC 1848 (Sh2-199) - has been investigated using a dual etalon Fabry-Perot optical spectrometer (DEFPOS) aatached to the 150 cm RTT150 telescope at TUBITAK National Observatory (TUG, Antalya, Turkey: 36 degrees 51' N; 30 degrees 20' E; elevation: 2547 m). All of our galactic Ha observations discussed in this paper were carried out during the nights of 2013 June 21-24 with exposure time of 3600 s. As main results the intensity, the full width at half maximum, and the radial velocity with respect to the LSR have been determined for each data set. The intensities, the radial velocities, and the line widths of the Ha emission line vary from 59.15 to 8923.44 R, -46.72 to + 54.07 km s(-1), and 31.4 to 48.01 km s(-1), respectively. The radial velocities and the half-widths of the HII regions and planetary nebulae determined from our measurements are found to be consistent with values given in literature, especially with those in Schneider et al. (1983) and Fich et al. (1990). (C) 2015 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim
Keywords: ISM; HII regions; planetary nebulae; general; instrumentation; adaptive optics; techniques; spectroscopic